THE PROBLEMS OF CREATING A HEALTHY PSYCHOLOGICAL ENVIRONMENT IN SOCIETY BULLYING IN EDUCATIONAL INSTITUTIONS THE IMPORTANCE OF LICENSING PSYCHOLOGISTS - Turaev Boboyor Baxtiyorovich (Journals Park Publishing, 2024)
The article describes the author's model of psychological service in the educational environment, reveals the main goals and objectives of its work, as well as innovative tools for collecting and analyzing the results.
Keywords: psychological service, educational environment, social and psychological climate in the team, bullying, stress audit.